New Therapies for Bipolar Depression and OCD - Nichols, Emma Hitt (MD Conference Express, 2014)
Several new therapies have shown promise in the treatment of adult and pediatric bipolar depression and obsessive compulsive disorder (OCD). This article discusses next generation in treatments for OCD, new data for pharmacotherapy of bipolar depression, as well as specific trials..